Polar Bear Hair Mercury Concentrations Southern Beaufort Sea 2004-2011 ... - Todd C Atwood; USGS Alaska Science Center, Polar Bear Research Program (U.S. Geological Survey, 2023)
These are data collected from polar bears from the southern Beaufort Seas during the spring and fall between 2004 and 2011. Data include individual ID, sex and age class, presence of dependent young, season of sample collection, total mercury concentration derived from a hair sample, estimate of annual diet proportion, and indices of body condition. ...